The Effect of Object Thickness in Numerical Reflectance and Transmittance using Finite Difference Time Domain (FDTD) (International Journal of Scientific Research and Management (IJSRM), 2024)
The electromagnetic waves could be simulated using finite difference time domain. This simulation method based on Maxwell equations. Here, the fields were spatially discretized along time discretization. This was the basic concept for updating the fields in every time step. Since the reflection and transmission of electromagnetic waves were the basic phenomena for optical studies of the waves in materials, we studied the reflectance and transmittance. In FDTD, the reflection and transmission could be calculated using Fourier transformation. We found that the thickness of the object which was inserted to the system affected the reflection and transmission significantly. If the thickness of the object became thicker, then there also increased the appearance frequency of the reflectance with the similar values. It was also happened to the transmittance.